Central Serous Chorioretinopathy in a Patient with Ulcerative Colitis with Pouchitis on Budesonide-EC. Issue 5 (May 2017) - Zullow, Samantha; Fazelat, Ahad; Farraye, Francis A.
Abstract : Article first Published online 21 March 2017